Դիոնիսիոս Արեոպագացին և Գրիգոր Նարեկացին - Թամրազյան, Հրաչյա («Նաիրի» հրատ.)
The writings ascribed to Dionysius the Areopagite have profoundly influenced medieval Armenian culture. Till now their relations with the works of David the Invincible, Nerses Shnorhali, Grigor Tatevatsi, Vanakan Vardapet, as well as, following Stepanos Siunetsi, the commentaries on them by Hamam Areveltsi, Yesayi Nchetsi, and Vahram Rabuni, that circulated in medieval Armenian schools, have been mentioned.
Keywords: Հայագիտություն